Pengaruh Lingkungan Kerja dan Loyalitas Kerja terhadap Kinerja Karyawan pada PT Bharaduta Jaya Sakti Jakarta Selatan - Tito Pangestu; I Made Aryata (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2026)
This study aims to determine the effect of Work Environment and Work Loyalty on Employee Performance at PT Bharaduta Jaya Sakti, both partially and simultaneously. The study uses an associative quantitative method with a population of 85 employees, and the sampling technique used is saturated sampling, where the entire population is treated as the sample. Data processing is done using SPSS version 25, with analysis methods including simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, partial t-test, and simultaneous F-test. The results show that the Work Environment has a significant partial effect on Employee Performance, with a t-count value of 7.949 (greater than the t-table value of 1.988) and a significance of 0.000 < 0.05. Work Loyalty also significantly affects Employee Performance, with a t-count value of 5.280 > t-table 1.988 and significance 0.000 < 0.05. Simultaneously, Work Environment and Work Loyalty significantly affect Employee Performance, with an F-count value of 31.754 > F-table 3.110 and significance 0.000 < 0.05. The coefficient of determination (R Square) of 0.436 indicates that 43.6% of Employee Performance is contributed by Work Environment and Work Loyalty.